Dekoracyjne formy. Przedmioty projektu Julii Keilowej na fotografiach Benedykta Jerzego Dorysa - Magdalena Wróblewska (Miejsce)
Benedykt Jerzy Dorys (1901–1990) was one of the most renowned portrait photographers in Warsaw of the 1930s. However, his activity was not confined solely to one kind of photography. He has created a documentation of the Jewish town Kazimierz on the Vistula, one of the most important reports of that time. He was engaged in commercial photography, mostly fashion for press and advertising. In the article the significance of this type of photography is analysed along with the example of the photos of some silver-plated objects, designed for distinguished Warsaw-based tableware companies (Fraget, Henneberg Brothers, Norblin) by a young sculptor, Julia Keilowa (1902–1943). Dorys’s photographs are stylistically consistent with the modernist design of the objects that give the impression of sculptures rather than everyday objects. In the analysis they are compared to some photographs of modern sculpture to emphasise the link between the commercial photography of the 1930s and the trends of the modernist visual art.